A novel α-conotoxin [D1G, ΔQ14] LvIC decreased mouse locomotor activity - Wang, Wen; Wang, Meiting; Wang, Huanbai; Xu, Weifeng; Wang, Conggang; Pei, Jie; Li, Xiaodan; Zhangsun, Dongting (Frontiers in Pharmacology, 2025)
Background and PurposeNicotinic acetylcholine receptors (nAChRs), which are expressed throughout the mammalian brain, mediate a variety of physiological functions. Despite their widespread presence, the functions of nAChRs are not yet fully understood. α-Conotoxins, which are peptides derived from the venom of marine cone snails, target different subtypes of nAChRs. Specifically, α-Conotoxins [D1G, ΔQ14] LvIC, identified from Conus lividus, have demonstrated strong activity on α6β4* nAChRs in vitro. However, the effects of [D1G, ΔQ14] LvIC have not been investigated in vivo. This study aims to examine the activities of [D1G, ΔQ14] LvIC and explore its potential mechanisms in vivo.MethodsThe study involved the injection of [D1G, ΔQ14] LvIC into the lateral cerebral ventricle (LV) of mice. Following this procedure, behavioral tests were conducted to assess changes in the mice’s behavior. To investigate the molecular alterations in the mice’s brains, untargeted metabolomics and label-free Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) were employed. Subsequently, Western blot (WB) and quantitative reverse transcription PCR (RT-qPCR) techniques were utilized to detect specific molecular changes induced by [D1G, ΔQ14] LvIC.ResultsThe injection of [D1G, ΔQ14] LvIC led to a decrease in locomotor activity in mice. This treatment also resulted in reduced expression of neuronal calcium sensor 1 (NCS-1) and neuroligin 3 (NLGN-3) in the prefrontal cortex (PFC), hippocampus (Hip), and caudate putamen (CPu). Both NCS-1 and NLGN-3 are crucial for neuronal development, synapse formation, and neuron activity, and their reduction is associated with decreased synapse strength. Despite these changes, results from the Morris water maze (MWM) indicated that [D1G, ΔQ14] LvIC did not impair the learning and memory abilities of the mice.ConclusionOur findings indicate that α-conotoxin [D1G, ΔQ14] LvIC significantly decreased locomotor activity in mice. Additionally, it altered gene expression primarily in areas related to neuronal development, synapse formation, and neuron activity, while also reducing synapse strength. This study first proposed that [D1G, ΔQ14] LvIC could modulate mice’s locomotor activity. However, further investigation is needed to understand the therapeutic effects of [D1G, ΔQ14] LvIC.